2015
DOI: 10.1021/jm501661f
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationship for the Oxadiazole Class of Antibiotics

Abstract: The structure-activity relationship (SAR) for the newly discovered oxadiazole class of antibiotics is described with evaluation of 120 derivatives of the lead structure. This class of antibiotics was discovered by in silico docking and scoring against the crystal structure of a penicillin-binding protein. They impair cell-wall biosynthesis and exhibit activities against the Gram-positive bacterium Staphylococcus aureus, including methicillin-resistant S. aureus (MRSA) and vancomycin-resistant and linezolid-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
76
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 30 publications
1
76
0
4
Order By: Relevance
“…We had previously shown that ND-421 has efficacy similar to that of linezolid (50% effective dose [ED 50 ] of 3.1 mg/kg for ND-421 versus 2.8 mg/kg for linezolid) in the mouse peritonitis infection model (16), a widely used model that is relatively rapid with simple endpoints (death or survival). This model provides rapid evaluation of in vivo efficacy, as it requires good pharmacokinetic (PK) properties to observe efficacy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We had previously shown that ND-421 has efficacy similar to that of linezolid (50% effective dose [ED 50 ] of 3.1 mg/kg for ND-421 versus 2.8 mg/kg for linezolid) in the mouse peritonitis infection model (16), a widely used model that is relatively rapid with simple endpoints (death or survival). This model provides rapid evaluation of in vivo efficacy, as it requires good pharmacokinetic (PK) properties to observe efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…3). However, the lower plasma-protein binding of linezolid (31% versus 98% for ND-421) (16,30) would appear to compensate for the other superior attributes of ND-421 to make its efficacy equivalent in the neutropenic thigh infection model. However, the in vivo efficacy of ND-421 was significantly better than that of linezolid in the NRS119 strain (linezolid resistant), with 1.7 ϫ 10 6 CFU/g or 1.49 log reduction compared to vehicle (P Ͻ 0.001), whereas linezolid resulted in no statistical reduction in bacterial counts (2.3 ϫ 10 7 CFU/g [P Ͼ 0.05], Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…18 An important and most familiar thiadiazole is acetazolamide, a carbonic anhydrase inhibitor, used in prevention and cure of acute altitude illness, 15 glaucoma, 15 idiopathic intracranial hypertension, 19 congenital myasthenic syndromes 20 and cystinuria. 21 Oxadiazoles too have been known to have fungicidal, 22 bactericidal, 23 and herbicidal activities 24 and the ring system is also present in a large number of bioactive molecules of varied pharmacological potential. 25 Inspired by the improved therapeutic options which the 'HAART' 26 (highly active antiretroviral) therapy has provided, in AIDS treatment it was thought of interest that a more preferable treatment options could emanate on joining the two active (or more than two) enzyme inhibitors together in the same molecular framework by adopting to such synthetic techniques which could allow these to become the part of the same molecule.…”
Section: Introductionmentioning
confidence: 99%